PENGARUH PERMAINAN LAGU DENGAN TEMA BINATANG TERHADAP PENGEMBANGAN KECERDASAN KINESTETIK ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Elsa Yonanda Hasibuan; Daviq Chairilsyah; Yeni Solfiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research is to know the the effect of games theme song with animals to kinesthetic Intelligence development 5-6 years old children in pembina kindergarten district pangean Kuantan singingi regency. The sample of population in this research is 5-6 years old to amount to 21 person’s. to collect the data is observasion technis. To analysis data used in this research is test-t. the result of research is obtained from the correlation r2=0,370 and the value of significance is 0,000. Because 0,370>0,05 then Ho rejected. The means of research the effect of games theme song with animals to kinesthetic intelligencedevelopment 5-6 years old children’s. the receive or reject hypothesis based on SPSS data windows for version 17 then can be seen from a comparison t value and t table is calculation of the test-t, seen that result t value -17,714 from the partiesof absolutely price, so the minus (-) price canot be used (Sugiyono, 2010). Then value 17,714. Dk=38 and the fault stage 5%=2,101, it can be seen the t price count greaterthan t table the first fault 5% (17,714>2,101). The mean Ho= were rejected and Ha=accepted. From the research I have conclusion that the games theme song with animals is be alternative to the teacher kinesthetic intelligence. Games theme song with animals to kinesthetic Intelligence development 5-6 years old children in pembina kindergarten district pangean Kuantan singingi regency the effect as big as 37% . which can be defined that developing a kinesthetic child intelligence be affected be other factors.Keyword: Kinesthetic Intelligence, Games Theme Song With Animals